A novel Competence Square based PV array reconfiguration technique for solar PV maximum power extraction. (15th October 2018) - Dhanalakshmi, B.; Rajasekar, N.
Highlights: A new Competence Square (CS) technique is presented for PV Array Reconfiguration. Challenges to attain maximum power in PV systems are discussed. Comparative analysis between various reconfiguration techniques is elucidated. Energy saving and income generation analysis are also outlined for assessment. Abstract: The ever growing interest on solar energy has augmented large solar power parks in the contemporary time. Even though the most commonly used Total Cross Tie (TCT) interconnection scheme minimizes mismatch losses, shade occurrence in large PV arrays drastically reduces the power output and invokes multiple power peaks in the P-V characteristics. To counteract the multiple peak issue, PV arrays are reconfigured either via electrical or physical reconfiguration techniques. In this regard, physical relocation methods are proven to be efficient and economical in achieving better shade dispersion since, it neither demands complex switching arrangements or high end controllers for reconfiguration. Therefore, this paper introduces an innovative Competence Square (CS) technique for physical rearrangement of PV panels in a TCT interconnection scheme. The method devised is a onetime relocation technique that follows a unique number pattern for relocating the PV panels. Moreover, various test results elucidate the effectiveness of the CS technique in effectively dispersing the shade over the entire PV array. For validation, four typical shade cases are considered and the results are comprehensively compared with the recently proved TCT and Dominance Square (DS) techniques. In addition, the proposed method is computationally easy and is adaptable for PV arrays of any size. Overall, CS technique has showed its eminence in obtaining smoother output characteristics, better fill factor, power enhancement and increased energy savings.